A reference governor for linear systems with polynomial constraints. (August 2022) - Burlion, Laurent; Schieni, Rick; Kolmanovsky, Ilya V.
Abstract: The paper considers reference governor design for a class of linear discrete-time systems with constraints given by polynomial inequalities and constant reference commands. For such systems, we propose a novel algorithm to compute the maximal output admissible set. The reference governor solves a constrained nonlinear minimization problem at the initialization and then uses a bisection algorithm at the subsequent time steps. The effectiveness of the method is demonstrated by two numerical examples.